2022
DOI: 10.1155/2022/3764444
|View full text |Cite
|
Sign up to set email alerts
|

Yunnan Baiyao Ameliorates Rheumatoid Arthritis in Rats by Shifting the Th17/Treg Cell Balance and Preventing Osteoclast Differentiation

Abstract: Yunnan Baiyao (YNB) is a traditional Chinese medicine that possesses anti-inflammatory effects. Previously, we have demonstrated the effects of YNB in rheumatoid arthritis (RA) animal models; however, the underlying mechanisms are unclear. In the present study, we aimed to investigate the effects of YNB on the T-helper (Th)17/T-regulatory (Treg) cell balance in a collagen-induced arthritis rat model orally administrated YNB or methotrexate, a widely used therapeutic agent for treating RA. Our results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Osteoclasts are largely responsible for joint bone deterioration in RA. Osteoclasts are participants of the monocyte/macrophage lineage and are the only cells involved in bone resorption by governing anabolic and catabolic processes of the osseous tissue (Ren et al 2022 ). During osteoclastogenesis, RANKL-induced RANK activation generates ROS, which further activates the RANKL-mediated signaling cascade (Kim et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts are largely responsible for joint bone deterioration in RA. Osteoclasts are participants of the monocyte/macrophage lineage and are the only cells involved in bone resorption by governing anabolic and catabolic processes of the osseous tissue (Ren et al 2022 ). During osteoclastogenesis, RANKL-induced RANK activation generates ROS, which further activates the RANKL-mediated signaling cascade (Kim et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also found that Yunnan Baiyao treatment significantly reduced the level of IL-17 in the serum of CIA rats, significantly increased the level of IL-10, reduced the number of Th17 cells, and increased the number of Treg cells in the spleen of CIA rats, thereby reducing the ratio of Th17/Treg cells. In addition, Baiyao decreased the expression of RANKL and OPG in the joint tissues of CIA rats and inhibited RANKL-induced OC production ( 191 ). This indicates that Yunnan Baiyao exhibits anti-RA activity by regulating the balance between Th17 and Treg cytokines and inhibiting OC activation.…”
Section: Immunotherapy For Rheumatoid Arthritis and Postmenopausal Os...mentioning
confidence: 99%
“…Such multi-component treatments not only improves the curative effect and avoids serious side effects or drug resistance but also adjusts the Th17/Treg cell ratio and promotes the rebuilding of a new immune balance. Many studies have demonstrated the effectiveness of traditional Chinese compounds as supplementary or alternative therapies for RA and PMOP (188,189). as summarised in Table 4.…”
Section: Chinese Medicinal Compoundsmentioning
confidence: 99%
“…Yunnan Baiyao is a famous proprietary medicine in the department of traumatology in China, with anti‐inflammatory, antibacterial, hemostatic, and phagocytic effects 72 . Ren et al 73,74 found that Yunnan Baiyao may additionally be used to decrease Th17 cells in the spleen of CIA rats, increase the variety of Treg cells, decrease the rate of Th17/Treg cells in the spleen of CIA rats, limit IL‐17 levels, and increase the levels of IL‐10 in the serum. Figure 3…”
Section: Intervention Of Other Tcm Therapies On Th17/treg Cells In Ramentioning
confidence: 99%